KEUNIKAN BUDAYA TIDUR INEMURI JEPANG - Budi Mulyadi (KIRYOKU, 2018)
The title of this research is The Unique Sleep Culture of Japan (Inemuri). Inemuri is a Japanese practice of sleeping in public places. Inemuri became a unique phenomenon and became a habit of Japanese people. Inemuri is a testament to the efforts and hard work of Japanese society. The purpose of this paper is to explain what is Inemuri, the cause of Inemuri, what is the uniqueness of Inemuri and the benefits of Inemuri. This research is a research model that use literary review research model to collect the dataThe paper shows that inemuri is the unique culture which happening in Japanese society, from salarymen until the students could sleep for a while at an unusual place like in the train, workplace or public places. One of the causes of inemuri is there is the fact that Japanese has most short sleeping time compared to other countries so that they get tired and feel sleepy after hard work and fall asleep in the train or workplaces. One of the uniqueness of inemuri is in Japan the inemuri is considered as the something normal. The people who do inemuri is considered as a hard worker. The Japanese people think there are many benefits from inemuri. One of them is inemuri can refresh the body and mind after hard work